A conjugated thiophene-based rotaxane: synthesis, spectroscopy, and modeling. - Zalewski, L; Wykes, M; Brovelli, S; Bonini, M; Breiner, T; Kastler, M; Dötz, F; Beljonne, D; Anderson, H; Cacialli, F; Samorì, P (2010)
A dithiophene rotaxane 1 subsetbeta-CD and its shape-persistent corresponding dumbbell 1 were synthesized and fully characterized. 2D NOESY experiments, supported by molecular dynamics calculations, revealed a very mobile macrocycle (beta-CD). Steady-state and time-resolved photoluminescence experiments in solution were employed to elucidate the excited-state dynamics for both systems and to explore the effect of cyclodextrin encapsulation. The photoluminescence (PL) spectrum of 1 subsetbeta-CD was found to be blueshifted with respect to the dumbbell 1 (2.81 and 2.78 eV, respectively). Additionally, in contrast to previous observations, neither PL spectra nor the decay kinetics of both threaded and unthreaded systems showed changes upon increasing the concentration or changing the polarity of the solutions, thereby providing evidence for a lack of tendency toward aggregation of the unthreaded backbone.